2014
DOI: 10.1080/09613218.2014.967977
|View full text |Cite
|
Sign up to set email alerts
|

Solid-wallU-values: heat flux measurements compared with standard assumptions

Abstract: The assumed U-values of solid walls represent a significant source of uncertainty when estimating the energy performance of dwellings. The typical U-value for UK solid walls used for stock-level energy demand estimates and energy certification is 2.1 Wm 22 K 21 . A re-analysis (based on 40 brick solid walls and 18 stone walls) using a lumped thermal mass and inverse parameter estimation technique gives a mean value of 1.3 + + + + + 0.4 Wm 22 K 21 for both solid wall types. Among the many implications for polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 11 publications
5
74
0
1
Order By: Relevance
“…(13). The present paper confirms but also complements the research done by Li [40] demonstrating that the measurements of heat flux in inhabited estates are very difficult. Li is describing large sources of errors, such as: poor contact between the heat flux sensor and the wall, difficulties to identify measurement points beyond thermal interference, etc.…”
Section: Analysis Of Results and Discussionsupporting
confidence: 86%
“…(13). The present paper confirms but also complements the research done by Li [40] demonstrating that the measurements of heat flux in inhabited estates are very difficult. Li is describing large sources of errors, such as: poor contact between the heat flux sensor and the wall, difficulties to identify measurement points beyond thermal interference, etc.…”
Section: Analysis Of Results and Discussionsupporting
confidence: 86%
“…For example, in-situ measurement of U-values in solid walls were found to be lower than those predicted [37,39,40], which affects the predicted energy savings and payback. However, while insulation of suspended timber ground floors was a Green Deal approved intervention measure [41], the heat-flow through this element, both uninsulated and insulated, is not well characterised at present, hindering retrofitting decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…However, on almost every occasion in which thermal performance has been measured, the values obtained have shown both significant variation within samples and overall divergence from predictions. For example, in situ U-value measurements have reported measured values typically 20% higher than predicted in cavity walls [1], but often lower than predicted in traditional stone and brick constructions [2][3][4][5][6]. Just as importantly, these studies have often revealed a large range in measured performance.…”
Section: Introductionmentioning
confidence: 99%